Patterns of Aquaporin 7 Expression in Normal Follicles and Follicular Cyst Follicles of Hanwoo - Chang-Woon Kim; Sunkyu Han; Changyong Choe (The Korean Society of Animal Reproduction and Biotechnology, 2015)
Alteration in ion channel or transporter expression levels affects cell volume which is produced by movement of water and ion across the plasma membrane. In particular, aquaporin (AQP) channels among ion channels play a crucial role in movement of water across the cell membrane. This study was performed to identify whether AQP expression is changed in bovine follicular cystic follicles using microarray, RT-PCR and Western blotting analyses. In microarray data, AQP4 expression was decreased, whereas AQP7 was increased in cystic follicles. Additional experiments were focused on the AQP7 expression increased in cystic follicles. The microarray data was confirmed by semi-quantitative polymerase chain reaction (PCR) and Western blot analysis. AQP7 mRNA and protein expressions were significantly increased in the cystic follicles (p<0.05). Application of estrogen (10 μg/ml) to bovine ovarian cells showed a trend of increase in AQP7 expression. From these results, we suggest that the increase in AQP7 expression in cystic follicles may play an important role in movement of water in bovine ovary. In addition, AQP7, a aquaglyceroporin permeating water and glycerol, could be a good target in development of methods for the cryopreservation of bovine ovary.